DENSITY OF THE ADHERENCE OF RESTORATIVE MATERIAL TO THE ENAMEL OF TEETH WITH DIFFERENT FORMATION OF CARIOUS CAVITY EDGE - Yu. V. Smeyanov; Yu. V. Lakhtyn; A. M. Romanyuk; O. V. Belonozhko (Східноукраїнський медичний журнал, 2019)
Introduction. At present, the question of the influence of carious cavity edge design on the density of the adherence of restorative material to the enamel remains discursive; there is some confusion in the open access publications on this topic.